STRUKTUR PASAR DAN KINERJA INDUSTRI TEKSTIL DAN PRODUK TEKSTIL (TPT) INDONESIA TAHUN 2007-2010 - Florentina, Florentina; Susilo, Y.Sri (Kinerja: Jurnal Bisnis dan Ekonomi, 2012)
This research aims to identify and analyze the market structure and the performance of Indonesian textileindustry in 2007-2010. Model and tools that used in this research are CR4 to analyze market structure,economic value added (EVA) to analyze performance and pooled data regression to analyze whether themarket structure affect the performance. Secondary data is used, in the form of time series and cross sectiondata contained in the annual report of 16 textile companies listed on Indonesia Capital Market, with observationperiod 2007-2010.The results of this research indicate that Indonesian textile industry market structure is tight oligopoly.Overall, Indonesian textile industry in 2007-2010 was able to produce economic value added. This conditionindicates that the performance of Indonesian textile industry is good enough. This research uses fi xed effectmodel in the pooled data regression analysis. The result of this analysis indicates that the market share(MS) variable as proxy of market structure is signifi cantly have negative effect to the EVA variable as proxy ofperformance. This effect is caused by a large market share that led to ineffi ciency in the companies and the oldindustrial machinery results on the decreasing productivity.Keywords: Market structure, performance, textile industry, economic value added, market share.